In Celebration of the Life of Shaykh Taha Jabir al-‘Alwani: May 12, 1935 – March 4, 2016 (American Journal of Islam and Society, 2016)
Shaykh Taha Jabir al-‘Alwani – professor of jurisprudence (fiqh)and the principles of jurisprudence (uṣūl al-fiqh); president of theSchool of Islamic and Social Sciences (SISS), which later becamethe Graduate School of Islamic and Social Sciences (GSISS); presidentof the Fiqh Council of North America, holder of the Imam Al-Shafi‘i Chair in Islamic Legal Theory at Corboda University;founding member and president of the International Institute of IslamicThought (IIIT); founder-member of the Council of the MuslimWorld League in Makkah; member of the Organization ofIslamic Cooperation’s Islamic Fiqh Academy in Jeddah; prolificwriter; and world renowned Islamic scholar and expert in Islamiclegal theory, jurisprudence, the principles of jurisprudence, Qur’anicsciences, and general Islamic thought – passed away on March 4,2016, at Ireland’s Shannon Airport while stopping over on his wayfrom Cairo to Washington, DC.An intellectual giant, friend, father, husband, and teacher, heleaves an immense void in the lives of many people. The Muslimworld mourns his loss and is the poorer for it.Shaykh Taha spent his life serving humanity and the truth,working tirelessly not only to elucidate the principles and methodologyof Islamic jurisprudence, but also to remove many of themyths and prejudices that had, over time, become entwined withMuslim cultural traditions and gained a strong foothold in the Muslimmind.Shaykh Taha always took account of Islam as it is being practisedin the modern world. For example, his seminal work Apostasyin Islam (2011), a masterful example of historical and scriptural ...